Design of AM self-capacitive transparent touch panel based on a-IGZO thin-film transistors - Wu, Kejun (2021)
In this work, we propose a novel active-matrix self-capacitance touch panel circuit. Each touch pixel contains only one thin film transistor. The principle of the touch event detection is to detect the voltage change, which is caused by the change of electrode capacitance. The voltage sensing by capacitance sensor is converted to capacitive digital data which compare with default value to judge whether the touch event is touched or not. The simplest structure increase maximizes the sensing pad area and reduce the parasitic effects. An array of 5×5 capacitive sensing active-matrix self-capacitive touch panel based on the proposed solution is designed and implemented. The potential for high precision and high reliability is proven in the measurement results.